2016
DOI: 10.3389/fimmu.2016.00241
|View full text |Cite
|
Sign up to set email alerts
|

T-bet and Eomesodermin in NK Cell Development, Maturation, and Function

Abstract: Recent reports give insights into the role of the T-box transcription factors, T-bet and Eomesodermin (Eomes), in NK cell biology. In this mini-review, we recapitulate the initial reports that delineate T-bet and Eomes as master regulators of NK cell development, maturation, and function. We discuss how T-bet and Eomes expression is regulated during NK cell development and peripheral maturation. Furthermore, we summarize the current literature on the role of T-bet and Eomes in the transcriptional regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 47 publications
5
105
0
Order By: Relevance
“…Recent reports have strengthened the significance of T-bet and Eomes in NK cell biology (47). In mice, T-bet and Eomes are necessary for maintenance of peripheral NK cells, their deletion in mature NK cells results in reversion to an immature phenotype (46).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recent reports have strengthened the significance of T-bet and Eomes in NK cell biology (47). In mice, T-bet and Eomes are necessary for maintenance of peripheral NK cells, their deletion in mature NK cells results in reversion to an immature phenotype (46).…”
Section: Discussionmentioning
confidence: 96%
“…It has been observed that the frequency of T-bet + cells and the level of T-bet expression per cell is significantly greater in the CD56 dim population compared to the CD56 bright population from peripheral human immune cells, contrary to Eomes expression pattern, suggesting the existence of a relationship among the expression levels of both transcription factors and the functionality of these cells (45). Thus, T-bet is related to terminal stages of maturation, while Eomes is downregulated during peripheral maturation (47). …”
Section: Introductionmentioning
confidence: 99%
“…In mice, these two ILC subsets appear to be developmentally distinct (6), because in addition to these CHILP data described above, genetic fate-mapping (fm) studies for Rorc2 , which encodes Rorγt, showed that mouse ILC3s are Rorc2 fm + whereas mouse Eomes + NK cells are Rorc2 fm − (68, 71, 72). In contrast, Scoville et al recently demonstrated that the putative human CILP (SLT stage 2b) population expresses RORγt and that human PB CD56 bright NK cells, which are NKp80 + EOMES + (4, 40, 59, 73, 74), constitutively express detectable RORC2 transcript (42). Thus, as opposed to mouse NK cells, at least some human NK cells would be fm + for RORC2 if such an experiment could be performed.…”
Section: Modeling Human Nk Cell Development In the Context And Era Ofmentioning
confidence: 93%
“…Most cNK cells in PB are CD56 dim , whereas CD56 bright cNK cells represent the minority of cNK cells in healthy donor PB, usually constituting ≤15% of the total circulating cNK cell pool (defined as Lin − CD56 + ). In healthy individuals, both PB cNK cell subsets constitutively express similar amounts of various intracellular and surface factors including T-BET, EOMES, the common IL-2 and IL-15 receptor beta chain (IL-2/15Rβ, CD122), 2B4, DNAM-1, NKG2D, NKp30, and NKp80 (Caligiuri, 2008; Collins et al, 2017; Lanier, 1998; Moretta et al, 2014; Simonetta et al, 2016). Moreover, in a general sense both subsets show the characteristic functions of cNK cells; i.e.…”
Section: The Breadth Of Human Nk Cell Diversitymentioning
confidence: 99%